Review Of Fiqh Siyasah Tanfidziyah On The Implementation Of The Performance Of The Bumiarum Village Government, Pringsewu Regency - Mayyadah, Putri; Nur, Efa Rodiah; Sukandi, Ahmad (JURNAL HUKUM SEHASEN, 2025)
The administration of village governance is a subsystem of the overall governance system, granting villages the authority to regulate and manage the interests of their communities. The successful implementation of advanced and prosperous village development is inseparable from the roles of both the government and the community. Therefore, in executing development initiatives oriented toward the welfare of the village community, village governance must consider social aspects and the most pressing needs of the villagers. Based on the principle of village autonomy, village governments have the right and authority to formulate and implement policies that serve as benchmarks for the success of village governance. This study aims to analyze the performance of the Bumiarum Village Government using the theory of Siyasah Tanfidziyyah. The method used in this study is a qualitative approach with a descriptive-analytical nature, involving observations and interviews with the Bumiarum Village Government and the community. Several policies have been implemented by the village government, including infrastructure development, financial management, and public services. However, the implementation of these policies has not been entirely equitable due to limitations in available resources. Furthermore, the performance of the village government remains suboptimal in providing public services. The findings of this study emphasize that the Village Head must continuously improve performance by enforcing stricter oversight of village officials, enhancing management capabilities, and increasing community awareness and participation in village governance. This will ensure that other policies can be effectively implemented, as analyzed through the perspective of Fiqh Siyasah Tanfidziyyah theory.